Analisis Permainan Sepak Bola: Pola Menyerang, Bertahan dan Transisi Timnas Indonesia U-19 Vs Bulgaria - Wibowo, Herlambang Fajar; widiyanto, Widiyanto; Nugroho, Mahir Dwi (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2021)
The aim of this research is to analyze the game patterns of the U-19 Indonesian National Team and can be an inspiration and reference for football coaches and staff, especially in paying attention to game patterns. This research uses document study method This research is a qualitative research using the observation method, and the data were collected through non-participant observation. The results of the research and discussion show the game patterns of the U-19 Indonesian National Team when doing defensive, attacking and transition moments. When defending, the national team did a defensive moment with a low zone with a 1-4-4-2 formation with flat technique, for an attacking moment the national team did a build up attack or build up from the goalkeeper to the front but sometimes takes a long ball from the goalkeeper to the attacker. For transitionmoments of attacking to defend the national team carried out a pattern of returning to the position zone, namely by returning to the low defense zone, for a moment of transition to defending to attacking the U-19 national team carried out a counterattack strategy. In this study, it was found that a lack of determination by the U-19 Indonesian national team players in implementing a negative transition strategy that to be late to return to base, it is advisable to increase the physical condition of the players with different training methods, because the physical condition needs of soccer players vary depending on position.